An Evaluation of Pediatric Out Patient Department (POPD) of a Private Dental College Hospital by Accompanying Parents of Child Patients - Khan, Md Asif Iqbal; Parvin, S; Aman, J; Mahmud, G; Anber, N; Chowdhury, TG (Update Dental College Journal, 2018)
Purpose:The Pediatric Out-patient-department (POPD) of a dental hospital deals with children with different tooth related complaints. Dental treatment of a child patient requires three way interactions between the child, the parent and the dental surgeon. Though health of the patient remains the top priority for caregivers, satisfaction with the delivery system is vital for long lasting doctor-patient relationship. Thepurpose of the study was to evaluate the performance of Pediatric OPD by the accompanying parents of children receiving treatment at the OPD of a private dental college hospital. Methods: A cross sectional study was carried out at the POPD of Sapporo Dental College Hospital, Uttara Model Town of Dhaka city during May-July 2017. Sampling was done by simple random sam- pling method .Data were collected from the parents of 122 children aged between 1-12 years by using a self-administrated questionnaire. Results: Majority of the participating parents were residents of Uttara Model Town or areas in the vicinity and were employed, educated and are middle are middle socioeconomic class. More than sixty percent (62.3 %) of the respondents were parents of children between 4-7 years of age. More than 90% of the patients had waiting time at the department between 0-30 minutes. Treatment cost was described as ‘low or ‘reasonable’ by 87% of the parents. Only 8.2% mentioned ‘unsatisfactory’ regarding the cleanliness of Pediatric OPD. More than 95% of the respond- ents expressed ‘Satisfactory’ and ‘good’ level of satisfaction with general performance of OPD and the treatment provided by the dental team. Conclusion: Parents expressed general satisfaction with the performance of Pediatric Department of Sapporo Dental College Hospital. Update Dent. Coll. j: 2018; 8 (1): 05-10